Some theoretical questions on differential teaching in secondary schools - Stulpinas , T. (Psichologija, 1969)
In the article the conception of differential teaching, its aim, place, the factors which the individual approach to pupils depend on as well as tasks for pupils are analysed. The author introduces the conception of differential teaching in a broad and a narrow sense. There are three perspective aims in differential teaching in the narrow sense. They are: the proximate, the medium and the distant one. The differential teaching is looked upon as a process. There are different combinations of physiological, psychological, pedagogical and social factors. According to the duration of action all the factors are divided into relatively constant and relatively temporary ones. The impossibility to level pupils is emphasized, the importance of the system and quality of tasks as well as the authors efforts to classify the differential tasks are shown up in the article.
Keywords: differential teaching; secondary school